Exploration of Phytoconstituents from Mussaenda roxburghii and Studies of Their Antibiofilm Effect. Issue 10 (20th September 2017) - Ghosh, Ranjit; Das, Manash C.; Sarkar, Arpita; Das, Antu; Sandhu, Padmani; Dinda, Biswanath; Akhter, Yusuf; Bhattacharjee, Surajit; De, Utpal Ch.
Abstract : In the context of ethno botanical importance with no phytochemical investigations, Mussaenda roxburghii have been investigated to explore it's phytoconstituents and studies of their antibiofilm activity. Four compounds have been isolated from the aerial parts of this plant and were characterized as 2 α, 3 β, 19 α, 23‐tetrahydroxyurs‐12‐en‐28‐oic acid (1 ), β ‐sitosterol glucoside (4 ), lupeol palmitate (5 ), and myoinositol (6 ). All these compounds were tested for antibacterial and antibiofilm activity against Pseudomonas aeruginosa . Compound1 exhibited three times more antibiofilm activity with minimum inhibitory concentration ( MIC ) at 0.74 mm compared to that of streptomycin. Molecular docking studies exhibited a very high binding affinity of1 with P. aeruginosa quorum sensing proteins and motility associated proteins viz . LasR and PilB, PilY1, PilT, respectively. Compound1 was also found to be non‐cytotoxic against sheep RBC and murine peritoneal macrophages at selected sub‐ MIC doses. Abstract :